Toxoplasmosis in Cats and Its Zoonotic Potential in and Around Bangladesh Agricultural University Campus - Sah, R. P.; Talukder, Md. H.; Rahman, A.K.M. Anisur; Hossain, Md B. (Nepalese Veterinary Journal, 2019)
Toxoplasmosis is a zoonotic disease, occurs in almost all warm blooded animals including human beings and is caused by a global protozoan intracellular parasite Toxoplasma gondii. It is estimated that one third of the world human population have been infected by this parasite. This protozoan causes a significant public health problem in humans and imposes considerable economic losses and damages to livestock. The final host is cat, Feliscatus, accounts for all of these significant burdens. Hence the present study was designed to determine the prevalence rate of T. gondii infection in cats and also to analyze the associated factors that were potential for human beings and livestock as well in the period from September 2014 to August 2016. Altogether 254 faecal samples from cat and 390 water samples were collected from Bangladesh Agricultural University (BAU) campus, farm and residential areas of BAU and were examined for presence of T. gondii oocysts at Department of Parasitology, BAU Mymensingh. The overall prevalence of T. gondii was 4.03% (26/644). Presence of T. gondii oocysts in faecal and water samples were 5.5% (14/254) and 3.08% (12/390), respectively. Adult cats had higher (6.7%) prevalence than young cats (3.8%). Summer season was found high prevalence (6.7%) of oocysts in cat faeces. Similarly drain water found higher positivity (6.67%) of oocysts. Therefore, this study concluded that the cats are contaminating the environment by shedding oocysts and then other animals can get the infection from grazing of contaminated grasses and drinking water. So eating undercooked goat, sheep and cattle meat; eating contaminated vegetables and drinking contaminated water are major sources for getting toxoplasmosis to human beings. Hence this disease has great zoonotic importance around BAU campus and therefore it is essential to create public awareness.